Match running performance fluctuations in elite soccer: Indicative of fatigue, pacing or situational influences? - Bradley, P. S.; Noakes, T. D. (Journal of Sports Sciences, 2013)
The aims of this study were to: (1) quantify match running performance in 5-min periods to determine if players fatigue or modulate high-intensity running according to a pacing strategy, and (2) examine factors impacting high-intensity running such as score line, match importance and the introduction of substitutes. All players were analysed using a computerised tracking system. Maintaining `high` levels of activity in the first half resulted in a 12% reduction (P < 0.01) in the second half for high-intensity running (effect size [ES]: 0.8), while no changes were observed in `moderate` and `low` groups (ES: 0.0-0.2). The `high` group covered less (P < 0.01) high-intensity running in the initial 10-min of the second versus first half (ES: 0.6-0.7), but this was not observed in `moderate` and `low` groups (ES: 0.2-0.4). After the most intense periods, players demonstrated an 8% drop in high-intensity running (P < 0.05) compared to the match average (ES: 0.2) and this persisted for 5-min before recovering. Players covered similar high-intensity running distances in matches with differing score lines but position-specific trends indicated central defenders covered 17% less (P < 0.01) and attackers 15% more high-intensity running during matches that were heavily won versus lost (ES: 0.9). High-intensity running distances were comparable in matches of differing importance, but between-half trends indicated that only declines (P < 0.01) occurred in the second half of critical matches (ES: 0.2). Substitutes covered 15% more (P < 0.01) high-intensity running versus the same time period when completing a full match (ES: 0.5). The data demonstrate that high-intensity running in the second half is impacted by the activity of the first half and is reduced for 5-min after intense periods. High-intensity running is also influenced by score line and substitutions but not match importance. More research is warranted to establish if fluctuations in match running performance are primarily a consequence of fatigue, pacing or tactical and situational influences.